O Canto do Tordo: violência, trauma e guerra na distopia Jogos Vorazes - Santos, Tainá Raue dos (2019)
Among the youthful literary works with high sales figures of the XXI century, the Hunger Games trilogy secured its place of prominence. The literary work has been a success of sales in several countries, with adaptations for films successful in box office. This feat draws attention to the trilogy, which belongs to the genus dystopia. Dystopias arose in the middle of the XX century, and are characterized by projecting a hypothetical future considering the worst possibilities for the problems of the context of society and the period in which they are written. The dystopian narrative is marked by the idealization of a catastrophic future, where humanity has reached the apex of its decadence, and the greatest fears have been realized. In recent years dystopian narratives have emerged in a return among the most successful releases in the vast field of literature. Most of these recent productions are included in the branch of Children's Literature, in this way, his speech is articulated seeking to reach this audience. In this sense, through the analysis of the trilogy we have as a first objective to discuss the relevance of literature itself, to the apprehension of contemporary debates, perceiving the rise of the dystopic genre throughout this century as a result of a historical process. In the plot of The Hunger Games saga are the memory and traumas consequent to a period of wars and scarcity, carried by the protagonist Katniss Everdeen, a feminine, adolescent person, exposed to the extreme situations of conflict and tension, that also reach great part of the society of Panem, the country where you live. In this place, the population is reminded daily by the government that its rebellion brought the war, thus forcing a submission of society, both for the remembrance of traumatic events and for the daily use of violence. Through the problematization of the trilogy, our second objective is to discuss the themes of the spectacularization of violence and the memory of wars, as well as the trauma resulting from these conditions, considering the presence of a woman in the protagonism. The narrative details are not considered as an isolated event but belong to a larger scope, considering the inspirations and intentions of the author Suzanne Collins, the dystopic trilogy is available as a narrative memory of the author's personal relationship with war and with American media discourses on the subject. On the other hand, through the analysis of the trilogy, we also discuss the relevance of literature itself to the apprehension of contemporary debates, perceiving the rise of the dystopic genre throughout this century as a result of a historical process.